PENERAPAN MGPS (Marine Growth Prevention System) PADA LAMBUNG KAPAL - Taubi Ahmad Fachroini; Dwisetiono (Hexagon Jurnal Teknik dan Sains, 2022)
MGPS (Marine Growth Prevention System) is a system a that hasbeen applied to siftling marine growth a growing,colonized sea-buliding hedges in the sea that can cause corrosion,which if not overcome drags on will result in damage to both the main engine and auxiliary enginengine. The growth of marine growth has resulted in a reduction in effective pipeline,that causing fluidic currents and the pressure loads received by the pipes to become larger,such as the water sea inlet and outlet pipes a part of the engine’s cooling system to become clogged. To prevent the occurence of a correlation by calculating the rate of JIS F057 sea water pipes and the heavy reduction in copper electrodes (Cu) type RRY17 based on the variability of a density current that result from increased ship speed